Undertown - Bukiet, Melvin Jules (Amulet Books, 2013)
Middle schoolers Timothy Murphy and Jessamyn Hazard careen downhill on a sailboat which was being towed through Manhattan and fall into the sewers, where they meet interesting characters before being caught by the evil "queen" of this underground society.